2004
DOI: 10.1103/physrevlett.93.267202
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Study of Spin Excitations in the Singlet Ground State ofSrCu2(BO

Abstract: High resolution, inelastic neutron scattering measurements on SrCu2(BO3)2 reveal the dispersion of the three single triplet excitations continuously across the (H,0) direction within its tetragonal basal plane. These measurements also show distinct Q dependencies for the single and multiple triplet excitations, and that these excitations are largely dispersionless perpendicular to this plane. The temperature dependence of the intensities of these excitations is well described as the complement of the dc-suscep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 21 publications
6
81
0
Order By: Relevance
“…͑18͒. Note that the renormalization at q = ͑ ,0͒ is, in fact, very small compared to that at q = 0, and solves the puzzle previously noticed, 13 as we shall explain below.…”
Section: Exact Numerical Diagonalizationmentioning
confidence: 64%
See 3 more Smart Citations
“…͑18͒. Note that the renormalization at q = ͑ ,0͒ is, in fact, very small compared to that at q = 0, and solves the puzzle previously noticed, 13 as we shall explain below.…”
Section: Exact Numerical Diagonalizationmentioning
confidence: 64%
“…12,13 This is the value we extracted before relying on the perturbative expression. 12 We have here calculated the renormalization coefficient at ͑ ,0͒, and shown that coefficient is quite different from that at ͑0,0͒; therefore, applying the same renormalization to both splittings 13 leads to an artificially large in-plane Dzyaloshinskii-Moriya coupling. This explains why the ratio appeared so large previously.…”
Section: Extracting the Couplings From Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature was varied between ambient and 25 K with a helium cooled cryostat. Two types of samples where used : [28]. The single crystals are naturally cleaved along the a À b plane.…”
Section: Methodsmentioning
confidence: 99%